LEGAL ANALYSIS ON THE CONSTRUCTION OF MEIKARTA PROJECT FROM THE LENS OF CONSUMER PROTECTION - Jonathan Christandy Simamora; Pinkan Puteri Adira; Zahra Aulia Putri (President University, 2022)
This study examines the legal aspects of the Meikarta project's construction in Indonesia from the perspective of consumer protection. Large-scale real estate development Meikarta has drawn attention because of claims of anomalies and violations of consumer rights. This essay attempts to evaluate the legal environment around the Meikarta project by looking at pertinent Indonesian laws and regulations concerning commercial agreements, consumer protection, and real estate development. Additionally, it assesses any effects on consumer rights and recourse options for impacted parties. With the use of this analysis, the study hopes to advance knowledge of the intricate legal issues pertaining to major construction projects and how they affect consumer protection in Indonesia.Keywords:Construction; Consumer; Consumer Protection; Consumer rights; Megaproject